1992
DOI: 10.1104/pp.99.4.1481
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Bundle-Specific Localization of Cytosolic Glutamine Synthetase in Rice Leaves

Abstract: Tissue localizations of cytosolic glutamine synthetase (GS1; EC 6.3.1.2), chloroplastic GS (GS2), and ferredoxin-dependent glutamate synthase (Fd-GOGAT; EC 1.4.7.1) in rice (Oryza sativa L.) leaf blades were investigated using a tissue-print immunoblot method with specific antibodies. The cross-sections of mature and senescent leaf blades from middle and basal regions were used for tissue printing. The anti-GS1 antibody, raised against a synthetic 17-residue peptide corresponding to the deduced N-terminal amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 25 publications
7
87
0
1
Order By: Relevance
“…Moreover, the close location of the CC-SE complexes to a small number of xylem elements appears to be a prerequisite for a direct xylem-phloem transfer of amino acids translocated from roots (Atkins, 2000). The enzymes of ammonium metabolism, including cytosolic GS1 Kamachi et al, 1992;Pereira et al, 1992), Asn synthetase (Nakano et al, 2000), and GDH (Tercé-Laforgue et al, 2004), are colocalized in the companion cells as well. Although there is no molecular evidence showing that amino acid trafficking takes place by broad affinity amino acid transporters in minor veins (Fischer et al, 1998;van Bel, 2003), phloem loading of Gln, Asn, and Glu from CC-SE complexes likely regulates nitrogen translocation in the sieve streams where these amino acids are maintained at the constant levels.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the close location of the CC-SE complexes to a small number of xylem elements appears to be a prerequisite for a direct xylem-phloem transfer of amino acids translocated from roots (Atkins, 2000). The enzymes of ammonium metabolism, including cytosolic GS1 Kamachi et al, 1992;Pereira et al, 1992), Asn synthetase (Nakano et al, 2000), and GDH (Tercé-Laforgue et al, 2004), are colocalized in the companion cells as well. Although there is no molecular evidence showing that amino acid trafficking takes place by broad affinity amino acid transporters in minor veins (Fischer et al, 1998;van Bel, 2003), phloem loading of Gln, Asn, and Glu from CC-SE complexes likely regulates nitrogen translocation in the sieve streams where these amino acids are maintained at the constant levels.…”
Section: Discussionmentioning
confidence: 97%
“…However, the whole leaves were ground in liquid N2 or an isotonic medium. It is hard to distinguish the subcellular fractions from the tiny vein network from those from the mesophyll cells of the leaves in these methods, as has been claimed in the case of the subcellular distribution of glutamine synthetase I in rice leaves [28].…”
Section: Discussionmentioning
confidence: 99%
“…The xylem is a water-conducting tissue and the phloem, composed of sieve elements and companion cells, is a food-conducting tissue. Phloem tissues are the site of glutamine synthetase I in rice leaves [28]. Carboxyarabinitol accumulates in the vacuoles in mesophyll cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is located in the vascular bundle of root and leaves, where it might play a role in the synthesis of glutamine for transport (Schjøerring et al, 1993) and in recycling of the NH $ released in production of the monomers for lignin biosynthesis (Raven, Wollenweber & Handley, 1992). Expression of GS " was not found in leaf mesophyll cells of Nicotiana tabacum (Carvalho et al, 1992) and Oryza sativa (Kamachi et al, 1992). Migge et al (1996) found that cytosolic GS activity in cotyledons of Lycopersicon esculentum appeared to be encoded by at least two sets of genes.…”
Section: Assimilation Of Gaseous Nitrogenous Pollutantsmentioning
confidence: 99%